DINAMIKA KARAKTERISTIK KOMITE AUDIT PADA AUDIT REPORT LAG - Anak Agung Putu Gede Bagus Arie Putu Gede Bagus Arie Susandya; Ni Nyoman Ayu Suryandari (Media Riset Akuntansi, Auditing & Informasi, 2021)
This study examines the role of the audit committee on audit report lag. The sample in this study was taken from all companies listed on the Indonesia Stock Exchange. The sample selection method using the purposive sampling method. By using multiple regression analysis techniques, it is found that the competence of the audit committee, number of members of the audit committee has a negative effect on the audit report lag. The higher the intensity of the audit committee meeting, the earlier financial reporting supervision occurs. High quality of financial reporting makes the audit period of the financial report audit shorter. The independence of the audit committee does not appear to affects the audit report lag. This is because the object of the examination of the financial statements itself is the annual report. On the other hand, the gender of the female audit committee has a negative effect on the audit report lag. The existence of female gender in the composition of the audit committee plays an important role in shortening the period for completion of audits by independent auditors.Penelitian ini mengkaji tentang peran komite audit terhadap audit report lag. Sampel dalam penelitian ini diambil dari seluruh perusahaan yang terdaftar di Bursa Efek Indonesia. Metode pemilihan sampel menggunakan metode purposive sampling. Dengan menggunakan teknik analisis regresi berganda diketahui bahwa kompetensi komite audit, jumlah anggota komite audit berpengaruh negatif terhadap audit report lag. Semakin tinggi intensitas rapat komite audit, maka semakin dini pengawasan pelaporan keuangan terjadi. Kualitas pelaporan keuangan yang tinggi membuat periode audit laporan keuangan menjadi lebih singkat. Independensi komite audit tampaknya tidak mempengaruhi audit report lag. Hal ini dikarenakan objek pemeriksaan laporan keuangan itu sendiri adalah laporan tahunan. Di sisi lain, jenis kelamin komite audit perempuan memiliki pengaruh negatif terhadap lag laporan audit. Keberadaan gender perempuan dalam komposisi komite audit berperan penting dalam mempersingkat jangka waktu penyelesaian audit oleh auditor independen.